Embriogenesis somatik pada kultur in vitro daun kopi robusta (coffea canephora var. Robusta chev.) - Murni, Pinta (Biospecies, 2010)
This research aims to induce tissue cells of robusta coffee leaves (Coffea canephoravar. Robusta Chev.) for embryogenesis through the addition of growth regulators kinetin and 2,4-D.The growth medium used is a solid Murashige-Skoog medium (MS). The added growth regulators areA = 10-7 Kinetin without 2,4-D, E = 5 x 10-6 M Kinetin and 2.5 x 10-5M 2,4-D; H = 5x10-6M Kinetin and5x10-5 M 2,4-D, I = 7.5 x 10-6M Kinetin and 5x10-5 2,4-D. Explants used were the second leaf from topbranch ortotroph of coffee plants with a size of about 0.5 x 1.0 cm. Observations were made on thepercentage of live explants, explant growth response including the formation of callus, organogenesis,and embryogenesis. The results showed that the planted explants are 100% alive, the growthresponse in the form of direct somatic embryogenesis occurred on the addition of Kinetin 10-7 without2,4-D. Other Treatment, E produced a response in the form of greenish compact callus, while twoother treatments, H and I, form whitish crumb/fragile structured callus. Thus, it was concluded that invitro culture of leaf tissue of Robusta coffee (Coffea canephora var. Robusta Chev.) on Murashige-Skoog (MS) medium with the addition of kinetin growth regulators and 2,4-D at different concentrationsproduce higher different growth rate. Response of growth that occurs is in the form of direct somaticembryogenesis, compact and crumb/fragile structured callus.